Suicide risk management : a manual for health professionals - Chehil, Sonia; Kutcher, Stanley P. (Chichester, West Sussex; Hoboken, NJ : Wiley-Blackwell, 2012)
Remote
This highly practical book explains how to identify and manage suicidal individuals and supports the health professional in assisting the patient to choose life rather than death.
Front Matter -- The Importance of Suicide Awareness and Assessment -- Understanding Suicide Risk -- Suicide Risk Assessment -- Putting It All Together: Tool for Assessment of Suicide Risk (TASR) -- Special Topics in Understanding and Evaluating Suicide Risk -- Suicide Prevention -- Suicide Intervention -- Post-Suicide Intervention: Caring for Survivors -- Care for the Carer: Death of a Patient by Suicide -- Clinical Vignettes for Group or Individual Study -- Appendix A: Tool for Assessment of Suicide Risk (TASR) -- Appendix B: 6-ITEM Kutcher Adolescent Depression Scale: KADS -- Appendix C: My Safety Plan -- Index.
Keywords: Psychiatry